Carrot and Stick: How Reemployment Bonuses and Benefit Sanctions affect Job Finding Rates - Bas van der Klaauw; Jan C. van Ours (Tinbergen Institute, 2010)
To increase their transition from welfare to work, benefit recipients in the municipality of Rotterdam were exposed to various financial incentives, including both carrots to sticks. Once their benefit spell exceeded one year, welfare recipients were entitled to a reemployment bonus if they found a job that lasted at least six months. However, they could also be punished for noncompliance with eligibility requirements and face a sanction, i.e. a temporary reducing of their benefits. In this paper we investigate how benefit sanctions and reemployment bonuses affect job finding rates of welfare recipients. We find that benefit sanctions were effective in bringing unemployed from welfare to work more quickly while reemployment bonuses were not.
Keywords: J64; C21; C41; 330; welfare to work; financial incentives; timing-of-events; dynamic selection; Aktivierende Arbeitsmarktpolitik; Ökonomischer Anreiz; Arbeitsmarktintegration; Arbeitsmarktpolitik; Beschäftigungseffekt; Rotterdam